The Present Condition of Sickle Cell Disease: An Overview of Stem Cell Transplantation as a Cure - Md. Sadique Hussain; Varunesh Chaturvedi (Georg Thieme Verlag KG, 2023)
Treatment of sickle cell disease (SCD) remains largely palliative. While it can enhance living standards, persons having SCD still suffer from extreme sickling crises, end-organ destruction, and reduced life expectancy. Increasing research has resulted in the recognition and advancement of stem cell transplantation and gene therapy as possible solutions for SCDs. However, there have been various factors that have hindered their clinical application. The more advantageous of the two, stem cell transplantation, is constrained by a small donor pool, transplant difficulties, and eligibility requirements. The current article reviewed the literature on SCDs, current treatment options, and more particularly the progress of stem cell transplants. It outlined various challenges of stem cell transplant and proposed ways to increase the donor pool using alternative strategies and modifications of regimen conditioning with minimal transplant-related toxicities and associated complications.